Stabilizing soft clay using geo-foam beads and cement bypass dust - Essam Farouk Badrawi; Mahmoud Samir El-kady (Underground Space, 2020)
Soft clays are usually classified according to their undrained shear strength, Su. Values of Su less than 12.5 kPa are associated with very soft clays. In addition to their low shear strength, soft clays exhibit high compressibility upon loading. Therefore, soft clays are considered to be problematic for foundation purposes. Geo-foam is an industrial material that is characterized by a very low unit weight (20 kg/m3 on average) compared to that of the soil. The density of expanded polystyrene (EPS) ranges from 1.0% to 2.5%, which results in a compressive strength ranging between 70 kPa and 140 kPa and an elastic modulus ranging between 5 MPa and 12 MPa. EPS geo-foam blocks are used in a wide range of geotechnical applications as a lightweight fill material.The main objective of this study was to investigate the geotechnical properties of soft clays containing geo-foam beads and cement bypass dust (CBPD). We also investigated the viability of preparing low-strength excavatable fill mixtures. To study the effect of (geo-foam beads + CBPD)/soft clay on the fluid-state and hardened properties of new fill, we conducted experiments on two groups of mixtures (A&B). Each mixture contained different ratios of geo-foam beads and CBPD so that we could study the effect of the additive on the flow consistency, dry unit weight, unconfined compressive strength, and shear strength of the mixture. The test results showed that the unconfined compressive strength of the studied mixtures without geo-foam ranged from 271.8 kPa to 1405.14 kPa at CBPD concentrations between 3.88% and 18.63%. The cohesion values for the group containing geo-foam ranged from 50 kPa to 20 kPa at geo-foam percentages between 0.32% and 1.35%. The friction angle of the group containing geo-foam ranged from 10 kPa to 22 kPa at CBPD percentages between 0.32% and 1.35%. Cement bypass dust can be successfully used to process self-compacting, self-leveling, excavatable and flowable fill material.